Last chance tourism: a decade review of a case study on Churchill, Manitoba’s polar bear viewing industry - D'Souza, Jamie; Dawson, Jackie; Groulx, Mark (Université d'Ottawa | University of Ottawa, 2021)
For over 50 years, Churchill, Manitoba has provided visitors an opportunity to see polar bears in their natural environment. Over the same time period, an increase in temperatures and related reductions in sea ice has negatively impacted the health of polar bears in the Western Hudson Bay. In 2008, the term ‘last chance tourism’ was coined, linking the demand to travel to the North with a desire to see these animals ‘before they are gone’. This creates a paradox as tourists require energy-intensive modes of transportation to reach the Arctic, thereby contributing to greenhouse gas emissions. This paper compares the polar bear viewing industry’s total greenhouse gas contribution and tourists’ knowledge about climate change with results from a 2008 study and discusses any changes over the last ten years. During the 2018 polar bear viewing season, greenhouse gas emissions were estimated to be 23,017 t/CO2, an increase from 2008. The results also indicated that although most tourists believe climate change is happening, fewer associate air travel to this — a similar finding identified ten years ago. Findings from this research show that consumption patterns have not changed despite a growing awareness of climate change and its impacts.
Keywords: climate change; polar bears; greenhouse gas emissions; last chance tourism; Churchill